2007
DOI: 10.1099/jmm.0.47389-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical valve endocarditis caused by Gemella morbillorum

Abstract: As the usual pathogen spectrum of a late-onset (.12 month post-operatively) prosthetic valve endocarditis is similar to normal valve endocarditis, with the exception of coagulase-negative staphylococcus, a prosthetic valve endocarditis caused by unusual bacterial pathogens represents a therapeutic and diagnostic dilemma. The lack of well established criteria or clinical experience for the management of such infections makes therapy and prognosis difficult to determine. A case of successfully treated Gemella mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…Pre-existing damaged heart valves, poor dental hygiene, intravenous drug abuse, and extensive dental procedures have been reported as the main predisposing risk factors for endocarditis due to G.bergeriae. [9,19] To date, approximately 45 cases of endocarditis associated with Gemella spp. have been reported in the literature [5,7,8,12,20] and among them only 8 were caused by G.bergeriae, including 7 adult cases and 1 pediatric case.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing damaged heart valves, poor dental hygiene, intravenous drug abuse, and extensive dental procedures have been reported as the main predisposing risk factors for endocarditis due to G.bergeriae. [9,19] To date, approximately 45 cases of endocarditis associated with Gemella spp. have been reported in the literature [5,7,8,12,20] and among them only 8 were caused by G.bergeriae, including 7 adult cases and 1 pediatric case.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review identified only four previous cases of G. morbillorum prosthetic valve endocarditis 3–6. Three of those patients were successfully treated with penicillin G for 6 weeks and gentamicin for 2 weeks3; ceftriaxone for 4 weeks and gentamicin for the first 2 weeks4; and with penicillin G plus rifampin for 6 weeks, gentamicin sulfate for the initial 2 weeks, and valve replacement, respectively 5. The fourth patient underwent valve replacement and was treated with vancomycin, gentamicin and rifampin; however, the patient died secondary to Escherichia coli bacteraemia during the postoperative period 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although G. morbillorum possesses very low virulence comparing to some other pathogens, it was reported to cause endocarditis [47]. The morbidity of G. morbillorum endocarditis remains a rare occurrence so far.…”
Section: Introductionmentioning
confidence: 99%